Correlation of Anthropometric Features with Peroneus Longus and Hamstring Tendons Graft Size for ACL reconstruction - Aditya Fuad Robby; Luthfi Hidayat; Rahadyan Magetsari (The Hip and Knee Journal, 2021)
Background: Reconstruction of the anterior cruciate ligament (ACL) is a commonly performed surgical procedure in recent years. Surgeons have to consider several factors including patient’s anthropometric variables to harvest the best graft. The hamstring tendon has its’ limitation, such as the tendon graft size deemed unfit especially for people of small statures. The peroneus longus tendon is a relatively new choice compared to hamstring. This study was conducted to know the correlation between anthropometric features with graft parameters or graft size in patients who underwent ACL reconstruction using peroneus longus and hamstring tendons.Materials and Methods: This cross-sectional study was performed in patients who underwent ACL reconstruction using peroneus longus or hamstring tendon autografts. We evaluated their anthropometric variables (age, gender, body mass index (BMI), height and weight) and correlated them with the graft diameter obtained during surgery. Post-operative results were assessed with Karlsson and Peterson Scoring System which represent the ankle function.Results: Twenty-three non-athletic patients underwent ACL reconstruction surgery. Patients with hamstring graft have the average height of 170 cm and 163.6 cm for the peroneal graft group. The average body weight of the hamstring graft group was 72.917 kg and the peroneal graft group was 68.82 kg. The measured BMI of the hamstring graft group was 25.2 kg/m2 and 7.833 mm of graft diameter in average, with 25.5 kg/m2 and 7.636 mm respectively for the peroneus graft group. There were strong positive correlations between weight and BMI with hamstring tendon graft diameter, but negative weak correlations with peroneus tendon graft diameter.Conclusion: We found that body weight and BMI correlate with the diameter of both peroneus and hamstring tendon grafts. Both autografts showed equally good functional results.